Penanggalan Mesir Kuno - Ridho Kimura Soderi (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2018)
Among human needs that are not as important as other primary needs is the need for calendars or commonly called calendars or dates. Calendar is a system of organizing units of time, for the purpose of marking and calculating time in the long run. Ancient Egypt had deep-rooted beliefs in dating, that is, through the routines of the nile's floods every year, which coincided with the emergence of sirirus stars in the east. The first dating system on this earth was the ancient Egyptian calendar system. The Egyptians first divided the day 24 hours, 12 hours for noon and 12 hours for night time.Keywords: Ancient Egypt, Calendar System, Season.